Comparative Evaluation of Vibratory Physiotherapy Methods in the Early Period after Cardiac Surgery - А. А. Eremenko; T. P. Zyulyaeva; D. V., Ryabova; А. P. Аlferova (Вестник анестезиологии и реаниматологии, 2022)
Postoperative respiratory complications in patients undergoing cardiac surgery occur in 20‒30% cases, and the most of them can be associated with ineffective cough and bronchial mucus evacuation.The objective. Comparative assessment of effectiveness and safety of methods for stimulating the evacuation of bronchial secretions using oscillatory PEP-therapy (Acapella Duet), oscillatory chest compression insufflator-aspirator “Comfort Cough Plus”, and the traditional method of manual chest percussion in the early period after cardiac surgery.Subjects and Methods. The prospective study included 120 cardiac surgery patients. They were divided into 3 groups (40 in each), depending on the type of the applied respiratory procedure. Distribution into groups was carried out by random selection. All procedures were performed 10‒12 hours after tracheal extubation. Before the procedure and 20 minutes after it, the efficiency of sputum discharge was assessed, gas exchange indices on room air breathing and maximum inspiratory lung capacity (MILC) were measured.Results. Ineffective bronchial mucus evacuating in the early period after tracheal extubation was observed in 86.7% of the patients. A single procedure of both PEP-therapy (Group 1) and mechanical cough stimulation (Group 2) led to improved sputum passage, as evidenced by an increase in the number of patients with productive cough by 4.25 times (p < 0.0009) and 5.3 times (p < 0.0007), respectively. In patients of Groups 1 and 2, an increase in MILC was observed (by 42.2% and 60.0%, respectively, p = 0.000001), the difference between the groups was statistically significant. In Control Group 3, with manual physiotherapy, the average increase in MILC was only 11.6%. Mechanical respiratory therapy procedures led to significant improvement in gas exchange variables, as evidenced by an increase in SpO2 in Groups 1 and 2 (p = 0.000009 and 0.000001, respectively) and a decrease in the proportion of patients with impaired oxygenating lung function (SpO2 below 92%) by 11 and 12 times, respectively (p < 0.01). The most significant changes were revealed in case of mechanical stimulation with aspirator-insufflator due to combination of two methods (oscillatory chest compression and lung inflation). In Control Group, no significant changes of gas exchange variables were observed.Conclusion: Mechanical vibratory methods for stimulating the bronchial secretion evacuation have significant advantages over classical manual chest massage in patients after cardiac surgery. Their positive effect on sputum passage, ventilatory parameters and gas exchange was noted, and the most pronounced effect was observed after oscillatory chest compression with insufflator-aspirator. The procedures were well tolerated and there were no complications associated with them.